The Great Exodus - Cai, Fang (China agricultural economic review, 2018)
Purpose The purpose of this paper is to review the process of rural labor reallocation and unfolds its growth effect through sufficiently supplying human resources, preventing diminishing return to capital, and increasing labor productivity. Design/methodology/approach The author surveys literature and statistics related to the subject to comprehensively picture the 40-year course of the shift and reallocation of agricultural surplus labor. Findings In the past 40 years, reforms in relevant areas have eliminated institutional barriers deterring labor mobility and allowed agricultural laborers to exit from low-productivity farming employment, migrate beyond rural-urban boundary and across regions, sectors, and ownerships, and enter higher productivity employment in non-agricultural sectors. As a result, resources allocative efficiency has been substantially improved, contributing a significant part to labor productivity growth and thus economic growth of the Chinese economy as a whole. Social implications To sustain this source of economic growth as far as China completes its transition from upper-middle income status to high-income status, deepening reforms is urgently needed. The author provides policy suggestions for further reform. Originality/value This paper enhances people’s understanding of the Chinese economic reform and its nature of efficiency and inclusion.